A Dimensional Approach to Schizotypy Conceptualization and Treatment - Cheli, Simone; Lysaker, Paul H. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This timely volume explores the range of personality traits and psychosocial deficits which are associated with the broadly defined construct of schizotypy. Describing schizotypy as a phenomenon that can be located on a continuum ranging from sub-clinical states to severe disorders, the editors have brought together experts in this field to discuss approaches to assessment, conceptualization, and treatment. This volume aims to provide a unique and clinically oriented perspective on schizotypy as a feature of personality and psychopathology. An essential resource for professionals, researchers, and academics the reader will gain knowledge of: Underlying maladaptive traits that can emerge as schizotypy Dimensional and transdiagnostic approaches to psychopathology Relationship to metacognition, mentalizing, attachment, self-criticism and interpersonal criticism This remarkable book brings together many influential scholars under the general rubric of dimensional approaches to schizotypy and can thereby serve as a real boon to both scientists and practitioners. Coverage of the current literature is extensive, and goes well beyond schizotypy research per se. Indeed, focal research on schizotypy as a psychopathological phenomenon is covered thoroughly yet is only one aspect of a much more comprehensive volume. Robert F. Krueger - University of Minnesota, USA In this thoughtful edited volume, Cheli and Lysaker build on these foundations by bringing together leaders in the field of schizotypy, personality and schizophrenia with the goal of translating complex research findings into practical, useful and clinically relevant information. They succeed in this goal with masterful integration of the research and clinical literature highlighting transdiagnostic processes central to the human experience such as metacognition, mentalizing, attachment, self- and interpersonal criticism that can be targeted in treatment. Carla Sharp - University of Houston, USA "A Dimensional Approach to Schizotypy" includes contributions from a number of researchers at the forefront of psychopathology and psychiatric nosology. The editors provide us with a 30,000-foot view of current-day schizotypy, accompanied by fascinating clinical theory and an updated discussion of transdiagnostic clinical implications. These chapters also include important new information on unique cultural perspectives, encouraging better representation of global populations, critical for the generalizability and public health impact of our research. Anna Docherty - University of Utah School of Medicine, USA.
Part 1 - Schizotypy as a feature of personality and psychopathology -- The Neurodevelopmental Considerations of Schizotypy -- Evolutionary aspects of schizotypy -- Conceptualization of Schizotypy within the Hierarchical Taxonomy of Psychopathology and other Nosologies -- Psychosocial Functioning in Schizotypy: Potential Links to Social, Cognitive, and Affective Processes -- Schizotypal disorder: Phenomenological perspectives on diagnosis, psychopathology, and psychotherapy -- Conceptualization and Assessment of Multidimensional Schizotypy -- Schizotypy: a crosscultural approach - Quinton Deeley -- Part 2 - Transdiagnostic mechanisms -- Understanding the phenomenology of schizotypy and schizotypal personality disorder: An application of the integrative model of metacognition -- Linking personality and psychopathology: a mentalization-based treatment framework for the understanding of schizotypy-related psychopathology -- The role of attachment processes in the psychosis-spectrum -- Compassion Focused Therapy and schizotypy: An exploration of an evolution informed biopsychosocial approach -- Interpersonal Diagnosis of Schizotypy -- Part 3 - Integrated interventions CBT for Schizotypy and Psychosis: the role of trauma -- Compassion Focused approach to working with problematic belief systems -- Addressing Schizotypy in Metacognitive Reflection and Insight Therapy -- Metacognitive Interpersonal Therapy for Schizotypal Personality Disorder -- Evolutionary Systems Therapy for Schizotypy: An Integrated Look at Attachment, Compassion and Metacognition -- Mentalization-based Treatment for Schizotypal Personality -- A view on the treatment of schizotypy in terms of psychoanalysis -- Clinical staging of schizotypal disorder: Preliminary considerations and treatment implications -- Schizotypy and hikikomori, a severe form of social withdrawal syndrome -- A disorder of engaging in the world: Concluding remarks and future directions (Conclusions).
Keywords: Psychology; Clinical psychology; Personality; Difference (Psychology).; Behavioral Sciences and Psychology; Clinical Psychology; Personality and Differential Psychology